The experiences, perspectives and needs of families raising neurodivergent twins: a multi-informant photo-elicitation exploratory study - Foley, Vicky; Kakoulidou, Myrofora; Sideropoulos, Vassilis; Phelps, Camilla; Pavlopoulou, Georgia (Frontiers in Psychology, 2025)
Despite research suggesting the importance of secure sibling relationships and the uniqueness of twin siblings’ connections, little is known about the experiences of twin siblings who have a neurodivergent twin. This study sought the voices of the twin/triplet siblings about their first-hand experiences of living with a neurodivergent co-twin/triplet. Research questions were co-designed with four mothers of neurodivergent twins/triplets, after consulting with 38 families of neurodiverse twins about their top research priorities. Fifteen photo-elicitation semi-structured interviews were conducted to explore both the neurotypical twins’ experiences and perceived needs and the mothers’ perceptions of the neurotypical twins’ experiences and perceived needs. Interpretative Phenomenological Analysis (IPA) was used to analyse the interview data. Themes across the neurotypical twins and their mothers included: (i) perception of the relationship between twins, (ii) perception of neurotypical twins as experts of their sibling’s neurodivergence, (iii) perception of the neurotypical twin’s struggles and needs. This study illustrates the everyday experiences of neurotypical twins with a neurodivergent co-twin from multiple perspectives. The themes demonstrate the closeness of their twin bond but also depicts the struggles sharing attention and time. A key difference in their perspectives was that mothers were more worried about their twins’ differences and conflicts, while twins felt mutual understanding and normalised these differences despite their conflicts. Future research should further explore twins’ life experiences and needs across the lifespan and include the perspectives of all family members, including those of neurodivergent twins as well as dyads and triads where all twins are neurodivergent.